Analisis Deskriptif Hasil Belajar Pembelajaran Tatap Muka dan Pembelajaran Online Menurut Gaya Belajar Mahasiswa - Anthony Anggrawan (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
Each higher education institution has a choice of learning models to be held, namely face-to-face learning, online learning, and blended learning. Face-to-face and online learning models have advantages and disadvantages in supporting student learning styles. Student learning styles not only represent what students like in learning, but also affect student learning outcomes. So it is not surprising, until now there is still a crossing of opinion in the achievement of learning, face-to-face learning or online learning that provides better results. This study provides an answer solution to learning English, whether face-to-face learning or online learning that is superior in cognitive learning outcomes according to student learning styles. The results of the descriptive analysis in this study concluded that students with auditory and visual learning styles taught with online learning models had higher average learning outcomes compared to students taught with face-to-face learning models; there is no difference in the average value of kinesthetic student learning outcomes between students who are taught by face-to-face learning with students who are taught by online learning; and in general the results of descriptive analysis show that online learning students are more successful in achieving learning outcomes compared to face-to-face learning students in learning English.